Contribution of asphalt rubber mixtures to noise abatement – time effect - Freitas, Elisabete F. (2010)
Wearing course layers with a rubberized asphalt binder have been lately recommended as a measure to mitigate noise. Their acoustical performance in an early age seems to be superior to that shown by conventional layers. Nevertheless, there is no deep knowledge in relation to their behavior throughout their lifetime. The research carried out aims at observing and studying this type of mixes. For this purpose, several road sections with gap-graded mixtures, two of which with rubberized asphalt, were selected. On each road section the tyreroad noise generated by two light vehicles was measured by means of pass-by tests. After three years, those tests were repeated under the same conditions. The results focused on the comparison of the noise level versus speed among layers at the same testing time and on the same layers with different ages. The results obtained three years ago showed that gap-graded asphalt rubber mixtures have a similar performance than that of other type of gap-graded thin mixtures. The same performance was observed in the recent tests. On average, an increase of 4.0 to 4.5 dB(A) was determined for the two surfaces with rubberized asphalt, which had the same increase on noise as the control surface.